Diode-Pumped Fluorescence in Visible Range From Femtosecond Laser Inscribed Pr:LuAG Waveguides - Sun, Lifei; Wang, Chao; Cui, Zemeng; Li, Ruonan; Cai, Yangjian; Ren, Yingying; Mackenzie, Mark D.; Kar, Ajoy K. (Frontiers in Physics, 2021)
Trivalent praseodymium (Pr3+) is the most established rare-earth ion for the direct generation of visible light. In our work, based on Pr-doped Lu3Al5O12 (LuAG) single crystal, cladding waveguides are fabricated by applying femtosecond laser inscription with different parameters. The main characteristics of the waveguides such as mode distributions, propagation losses are investigated. The investigations on confocal micro-photoluminescence enable us to illustrate femtosecond laser induced modifications in Pr:LuAG matrix. The waveguides are further pumped at a wavelength of 450 nm with an InGaN laser diode. Guided fluorescence emissions in visible range covering green, yellow-green, orange and red are obtained with a maximum slope efficiency of 4×10-4.